Estudio comparativo del maíz morado (Zea mays L.) y simvastatina en la reducción de lípidos séricos de pacientes diabéticos normotensos con dislipidemia - Ronceros, Gerardo (2012)
Objectives: To determine the effectiveness of Peruvian purple corn (Zea mays) administration in serum lipids levels reduction (hypolipidemic effect) in non hypertensive diabetic patients with dyslipidemia; to compare hypolipidemic effect of Peruvian purple corn and simvastatin. Design: Clinical essay. Setting: Instituto de Investigaciones Clinicas, Facultad de Medicina, Universidad Nacional Mayor de San Marcos, Lima, Peru. Participants: Non hypertensive dyslipidemic diabetic patients. Interventions: Between January and October 2006 two groups of 15 non hypertensive dyslipidemic diabetic patients were randomly formed, patients with recent diagnosis, without previous treatment and without chronic complications; one group recieved simvastatin 40 mg/day and the other group Peruvian purple corn (dehydrated and micropulverized pills 1g/day) for 30 days. Patients had low fat diet with weekly nutritional evaluation and received conventional hypoglicemic treatment with glibenclamide. Serum lipids, glucose, glycosylated hemoglobin, hepatic and renal function tests were done before and after treatment. Statistical analysis used Student t test with 95% confidence interval. Main outcome measures: Serum cholesterol, triglycerids and glucose levels variation. Results: There was reduction in both groups of total cholesterol, LDL cholesterol, triglycerides and fasting glucose serum levels; HDL cholesterol serum levels increased. Comparing basal and post treatment results for purple corn, there was significant reduction of triglycerides levels and significant increase of HDL cholesterol. In the simvastatin group there was significant statistical reduction of total cholesterol, LDL cholesterol, triglycerides and statistically significant increase in HDL cholesterol compared with basal levels. Compared with simvastatin purple corn optimized glucose control more significantly. There was significant statistical difference for post treatment values of total cholesterol, LDL cholesterol, HDL cholesterol and triglycerides in favor of the group that received simvastatin compared with purple corn. Conclusions: At doses studied Peruvian purple corn was effective in reducing triglyceride levels, increasing HDL cholesterol and optimizing glucose control in non hypertensive diabetic patients. Simvastatin was more efficacious than Peruvian purple corn in treatment of dyslipidemia without important effects on glycemia.